BEĞAVÎ'NİN MEÂLİMU'T-TENZÎL İSİMLİ TEFSİRİNDEKİ HADİSLERİN TAHRİÇ VE DEĞERLENDİRİLMESİ (ÂL-İ İMRÂN SÛRESİ 1-120. AYETLER) - GÜNEŞ, NEBAHAT (Fırat Üniveristesi, 2017)
Meâlimu't-Tenzîl, müfessir, muhaddis ve aynı zamanda fakîh olan Beğavî'nin en tanınmış eseridir. Beğavî, tefsirini rivayet usûlüne göre yazmıştır. Hadisçi olması sebebiyle ayetlerin tefsirinde hadislere de yer vermiştir. Biz bu çalışmamızda müellif hakkında kısaca bilgi verdikten sonra Beğavî'nin Meâlimu't-Tenzîl adlı eserinde Âl-i İmrân sûresinin (1-120. ayetler) tefsirinde yer alan ilk yetmiş dört hadisi inceledik. Bu bağlamda hadislerin tahricini yaptıktan sonra sıhhat değerlendirmesinde bulunduk. Tahricini yaptığımız hadis sayısı 74'tür. Münekkit muhaddislerin kanaatlerinden hareketle şunları söyleyebiliriz: Bu hadislerin 43'ü sahîh, 3'ü hasen, 20'si zayıf, 2'si mevzûdur. Hakkında hüküm verilemeyenlerin sayısı da 6'dır. Dolayısıyla müellif, hadisleri büyük oranda (% 58.1) sahîh rivayetlerden seçmiştir. Hasen hadislerin tüm hadislere oranı, % 4.05; zayıf rivayetlerin oranı, % 27.02; mevzû rivayetlerin oranı da % 2.7'dir. Hakkında hüküm verilemeyenlerin oranı ise % 8.1'dir. Rivayetlerin 53 tanesi Kütüb-i Tis'a'da, 3'ü diğer hadis kaynaklarında, 13'ü hadis kaynakları dışındaki kaynaklarda geçmektedir; 3'ü de kaynaklarda rastlayamadığımız rivayetlerdendir. Buna göre Kütüb-i Tis'a'da geçen hadislerin tüm hadislere oranı, %71.62'dir. Kütüb-i Tis'a dışındaki diğer hadis kaynaklarında geçen hadislerin oranı, % 4.05; hadislerin % 17.56'sı da diğer kaynaklarda geçmektedir. Kaynaklarda rastlayamadığımız rivayetlerin oranı da % 4.05'tir. 74 hadisin 53'ü (%71.62) isnadlı, 21'i (%28.37) de isnadsız zikredilmiştir. Anahtar Kelimeler: Beğavî, Meâlimu't-Tenzîl, Hadis, Kütüb-i Tis'a, Tahrîç,İsnad.

Maâlim at-Tanzil is the most well-known work of al-Baghawi who is a scholar of tafsir, hadith and fiqh. Al-Baghawi wrote his tafsir based on the method of riwaya (narrative reports). Since he was also a scholar of hadith, he included hadiths in the exegesis of the Qur'anic verses. In this study, after giving a brief information about the author, we examined the first seventy-four hadiths which exist in the tafsir of surah Al 'Imran (the verses between 1-120) in Maâlim at-Tanzil, the tafsir of al-Baghawi. In this regard, after making the verification of hadiths we evaluated their authenticity. The number of hadiths that we made their verification is 74. Based on the opinions of the critic hadith scholars, we can assert that 43 of hadiths are sound (sahîh), 3 of them are good (hasan), 20 of them are weak (da'if) and 2 of them are fabricated (mawdu'). The number of hadiths that cannot be adjudicated is 6. Therefore, the author selected the hadiths mainly from the sound narrations (58.1%). The proportion of the good hadiths is 4.05%, the weak hadiths is 27.02% and the fabricated hadiths is 2.7%. The proportion of those that cannot be adjudicated is 8.1%. 53 of the narrations exist in al-Kutub at-Tis'ah (the nine major hadith collections), 3 of them are in the other hadith sources and 13 of them exist in the sources other than hadith. 3 of them are narrations that we could not identify their sources. Hence, the proportion of hadiths that exist in al-Kutub at-Tis'ah to all hadiths is 71,62%. The proportion of hadiths that exist in other hadith sources is 4,05% and 17,56% of hadiths exists in the sources other than that of hadith. Finally, the proportion of the narrations that we could not identify their sources is 4,05%. 53 of the hadiths out of 74 (71,62%) are reported with a chain of transmitters (isnad) and 21 of them (28,37%) are reported without a chain of transmitters. Key Words: al-Baghawi, Ma'alim at-Tanzil, Hadith, al-Kutub at-Tis'ah,Extraction, Chain of transmitters
The extraction and evaluation of hadiths in the commentary of al-Baghawi titled maalim at-Tanzil (1st – 120th verses of surah Âl-i İmran)
Keywords: Din